Smokers' sexual behavior and their satisfaction with family life - Eiji Yamamura (Economics and Econometrics Research Institute (EERI), 2012)
It has been recently recognized that there is difference of preference between smokers and non-smokers. That is, smokers tend to be more impatient and prefer immediate benefits compared with non-smokers. If people follow their primitive instincts they will engage in sexual behavior. Hence, impatient people are more likely to have sex because it is difficult for them to control their instincts. However, for married people, having sex with a spouse is considered to be an investment in family life to ensure a good marital relationship. Therefore, sex with a spouse is considered to result in a long-term benefit, rather than an immediate benefit. This paper used individual-level data from Japan to investigate how sexual behavior differs between smokers and non-smokers. After controlling for various individual characteristics, the important findings are as follows. (1) Frequency of sex is positively associated with family satisfaction; (2) unmarried smokers are more likely to have sex than unmarried non-smokers; and (3) married smokers are less likely to have sex than married non-smokers. These findings regarding smokers' sexual behavior are congruent with the characteristics of smokers suggested in existing literature.
Keywords: D30; D63; H29; Z13; 330; Smoker; Time preference; Sexual behavior; Satisfaction